Economic importance of electronic payments developments in trade (Journal of Economic Research & Business Administration, 2015)
Resume. In this article conditions of electronic trade, and also stages of the organization and improvement of national system electronic payments in RK are considered.
Keywords: еlectronic trade; multiemitentny system; mobile trade; digital goods.